2022
DOI: 10.3390/ma15144907
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Sound Insulation and Dual Equivalent Negative Properties of Acoustic Metamaterial with Distributed Piezoelectric Resonators

Abstract: Aiming at the unsatisfactory sound transmission loss (STL) of thin-plate structures in the low-mid frequency range, this paper proposes an acoustic insulation metamaterial with distributed piezoelectric resonators. A complete acoustic prediction model is established based on the effective medium method and classical plate theory, and the correctness is verified by the STL simulation results of the corresponding acoustic-structure fully coupled finite-element model. Moreover, the intrinsic relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Bai [18] modeled and simulated the vibration and sound radiation of a double-layer cylindrical shell system based on the impedance analysis method, and found that the solid ribbed plate has a certain effect on the sound insulation of the double-layer cylindrical shell in the medium-and high-frequency regions, and no significant effect in the frequency area below 100 Hz. Zhang et al [19] proposed an acoustic isolation metamaterial for distributed piezoelectric resonators, derived an acoustic prediction model, and verified its correctness by the STL simulation results of the corresponding acoustic-structural fully coupled finite element model.…”
Section: Introductionmentioning
confidence: 95%
“…Bai [18] modeled and simulated the vibration and sound radiation of a double-layer cylindrical shell system based on the impedance analysis method, and found that the solid ribbed plate has a certain effect on the sound insulation of the double-layer cylindrical shell in the medium-and high-frequency regions, and no significant effect in the frequency area below 100 Hz. Zhang et al [19] proposed an acoustic isolation metamaterial for distributed piezoelectric resonators, derived an acoustic prediction model, and verified its correctness by the STL simulation results of the corresponding acoustic-structural fully coupled finite element model.…”
Section: Introductionmentioning
confidence: 95%
“…VTL 20 log a ( ) a = × (7) in which a1 and a2 represent the measured values of the output and input acceleration sensors, respectively, and the installation positions of the sensors are shown in Figure 10.…”
Section: Evaluation Of Vibration Suppression Performance By Simulatio...mentioning
confidence: 99%
“…Metamaterials are artificial composite materials with a periodic arrangement of elements and remarkable physical properties that do not exist in natural materials. Welldesigned metamaterials exhibit excellent properties in many fields, such as mechanics [1][2][3][4], acoustics [5][6][7][8][9], optics [10][11][12][13], and electromagnetics [14][15][16]. Due to these special properties, metamaterials have been widely used in transportation [17,18], the automobile industry [19,20], aerospace [21,22], and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic finite element simulation model was built based on the basic theory of pressure acoustics [ 43 , 44 ], and it supplied the foundation to investigate the sound insulation mechanism of the composite material by analyzing the distributions of the SPL.…”
Section: Acoustic Finite Element Simulation Modelmentioning
confidence: 99%
“…Meanwhile, the weighted STL with the 1/3 octave band was treated as the evaluation criterion for comparing the sound insulation performance with various influencing parameters [ 40 , 41 , 42 ]. The finite element simulation model was first built based on the basic theory of pressure acoustics [ 43 , 44 ], which could research the sound insulation mechanism of the composite material through analyzing the distribution of the sound pressure level (SPL). Afterward, the influences of the parameters on the STL of the composite materials were investigated one by one, such as the density of the composite rubber and that of the HGM, the acoustic velocity in the polymer and that in the inorganic particle, the frequency of the incident wave, the thickness of the sound insulator, and the diameter, volume ratio and hollow ratio of the HGM.…”
Section: Introductionmentioning
confidence: 99%